An Active Suspension System of One-wheel Car Models Using Fuzzy Reasoning - YASHIMURA, Toshio; HINO, Junichi; KURIMOTO, Masao; TAKEI, Kazuyoshi (Transactions of the Japan Society of Mechanical Engineers Series C, 2001)
This paper is concerned with the design of an active suspension system for one-wheel car models using fuzzy reasoning. The proposed active control for the suspension is derived as a linear combination of the defuzzificated values of the outputs in single input rule modules. The model is approximately described as a two-degrees nonlinear system subject to a random input. The experimental result shows that the proposed active suspension system more improves the vibration response of the vehicle body than a skyhook damper suspension system.